Ensifer (Sinorhizobium) fredii Interacted More Efficiently than Bradyrhizobium japonicum with Soybean - Pastorino, Graciela Noemí (2015)
Aims:The purpose of this work was to compare the efficiency of Bradyrhizobium japonicum and Ensifer fredii to infect and develop nodules on soybean. Furthermore we also evaluated the competitive ability of both species and how this was altered by the plant genotype and the soil pH. Study design: The design of the experiments was completely at random and the number of replicates was different on each of the different experiments tested. Place and Duration of Study: Department of Medicine (Medical Unit IV) and Department of Radiology, Services Institute of Medical Sciences (SIMS), Services Hospital Lahore, between June 2009 and July 2010. The whole work lasted about a year and a half. Methodology: Roots of inoculated soybean plants were fixed and the number of infection initiation sites was evaluated by means of microscopic observation. The number of nodules developed by inoculated plants was also evaluated. Results: Bacteria were equally effective at developing infection initiation sites on soybean however, E. fredii induced more nodules than B. japonicum, probably due to the fact that E. fredii is more efficient than B. japonicum at nodulating soybean. However, Bradyrhizobium was more competitive than E. fredii which was unrelated to the soybean genotype but altered by the soil pH. Under the conditions described E. fredii was less competitive than B. japonicum probably due to the high cultivar-rhizobia specificity. Conclusion: Therefore, we concluded that E. fredii was as efficient as B. japonicum at nodulating soybeans. However Bradyrhizobium was a better competitor though this is affected by the plant genotype and the soil pH. The selection and use of fast growing rhizobia in inoculant production seems to depend on broadening the genetic base of soybean or in selecting cultivars with specificity for fast growing rhizobia.